PENERAPAN METODE BERMAIN PERAN UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN IPS POKOK BAHASAN JENIS‐JENIS USAHA EKONOMI DI SDN NGADILUWIH 02 KEDIRI - zulfa nairurohmah; Chumi Zahroul (Pedagogi : Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 2016)
The  Social  Scients  Subject  learning  activities  in  SDN  Ngadiluwih  02  Kediri  yet  using  a variety  of  learning  methods.  According  to  the  observation  of  prasiklus  known  that  the activity  and  student  learning  outcomes  have  not  been  included  in  both  criteria. Precentation of student activity in the prasiklus in highly active criteria is12% (3 students), in the active criteria is 16% (4 students), in the quite active criteria is 56% (14 students), in the  low  active  criteria  is  16%  (4  students).  The  means  of  student  learning  activity  in prasiklus  is  56%  (quite  active  criteria).  Precentation  of  student  learning  outcomes  in  the very good criteria is 24% (6 students), in the good criteria is 24% ( 6 students), in the good enough  is  36%  (9  students),  in  the  not  good  is  16%  (4  students).  The  means  of  student learning  outcomes  in  prasiklus  is  68  (good  enough  criteria).Based  on  these  findings  the need  for  a  more  varied  teaching  methods  with  emphasis  on  student  activity  and  provide opportunities  for  students  to  develop  their  learning  abilities  to  the  fullest.  In  accordance with  these  problems,  the  goal  of  this  research  is  to  improve  the  activity  and  student learning  outcomes  in  class  V  through  the  application  of  learning  methods Role  Playing IPS Highlights  Types  of  economic  activities  in SDN  Ngadiluwih  02  Kediri.  This  type  of  research is classroom action research (PTK) are conducted in two cycles. The results obtained in this study  indicate  that  through  the  implementation  of  Role  Playing  method  can  increase  the activity  and  student  learning  outcomes.  The  average  activity  of  students  in  prasiklus  is 56,4%  (quite  active  criteria).  In  the  first  cycle  increased  to  70,8%  (active  criteria).  In  the second  cycle  increased  again  to  80,96%  (highly  active  criteria).  The  means  score  on  the student  learning  outcomes  prasiklus  is  68  (criteria  quite  well).  In  the  first  cycle  increased to 73.2 (good criteria). In the second cycle increased again to 83.18 (very good criteria).  Keywords:  Role  Playing  Method,  student  lerning  activity,  student  learning  outcomes, classroom action research.